Human Papillomavirus (HPV) Genotyping of Cutaneous Warts in Greek Children. Issue 6 (4th April 2013) - Giannaki, Maria; Kakourou, Talia; Theodoridou, Maria; Syriopoulou, Vassiliki; Kabouris, Marios; Louizou, Eirini; Chrousos, George
Abstract The human papillomavirus (HPV) infects the squamous epithelium of the skin and produces common warts, plantar warts, and flat warts, which occur commonly on the hands, face, and feet. The objective of this study was to determine the presence of HPV in warts in children in order to associate the virus with the disease. Sixty‐eight children with clinically diagnosed cutaneous warts were recruited. Skin biopsy samples were examined and DNA was extracted using a commercially available kit. To distinguish between the HPV types, we used a specific pair of primers to amplify the HPV DNA. Polymerase chain reaction amplification of the L1 region was followed by restriction fragment length polymorphism analysis and Luminex xMAP technology. HPV 57 was the predominant type in our study, although the detection of the high‐risk HPV type 16 in 33% of our positive samples indicates the presence of mucosal high‐risk HPV types in the skin of children. It seems that the newly introduced Luminex assay maximized the discrimination of genotypes even in the case of multiple HPV infections. Or findings also suggest the presence of high‐risk HPV types in cutaneous warts.